2020
DOI: 10.3390/su12062234
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Food Packaging Attributes to Influence Consumers’ Decisions to Sort Waste

Abstract: Food packaging waste is a valuable resource for material recovery, if it is properly separated and sorted by consumers. The packaging itself may have the potential to assist consumer sorting by, for example, communicating a correct sorting practice. This is partly due to the fact that the sorting of packaging waste, which is a habitual behavior of consumers, can be perceived as being confusing and inconvenient. Consumers can, therefore, choose not to sort. It is argued that material recovery could be enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 63 publications
0
30
0
2
Order By: Relevance
“…Our analysis suggests that a labelling system that enables the appropriate purchase and waste management behaviours is needed, alongside improvements to BCPP waste collection and processing. Preliminary results already show that designing food packaging based on user-centered needs may promote more desirable waste disposal behaviours [68]. To promote the purchase of BCPP, environmental impacts need to be better communicated on packaging.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis suggests that a labelling system that enables the appropriate purchase and waste management behaviours is needed, alongside improvements to BCPP waste collection and processing. Preliminary results already show that designing food packaging based on user-centered needs may promote more desirable waste disposal behaviours [68]. To promote the purchase of BCPP, environmental impacts need to be better communicated on packaging.…”
Section: Discussionmentioning
confidence: 99%
“…Food packaging waste sorting right from household waste at source forms a crucial part of waste management systems [55,80]. A study by Nemat et al [81] showed that food packaging design possesses the potential to influence consumer behaviour when making decisions on disposal post use, however current food packaging is not adequately doing so. Through properly communicating to the consumer, packaging can convey specific information with regards to separating and sorting of the packaging post use.…”
Section: Collecting and Sortingmentioning
confidence: 99%
“…Some public procurement options have focused in the reduction of plastic use (Neto 2020), to prevent both waste and possible endocrine problems (WHO 2013). Often packages are larger than necessarydue to packaging technology and marketing -and, in many products, this could be avoided (Nemat et al 2020). For instance, in Ames, the LCA has shown how replacing bottled water with tap water may reduce plastic waste by 47%.…”
Section: From the Whole To The Parts Agroecological Drivers To Reduce The Climate Impact Of School Canteensmentioning
confidence: 99%